2018
DOI: 10.3389/fmed.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Common Evaluations of Disease Activity in Rheumatoid Arthritis Reach Discordant Classifications across Different Populations

Abstract: ObjectivesThe classification of disease activity states in rheumatoid arthritis (RA) can be achieved through disease activity indices, such as the Disease Activity Score in 28 joints erythrocyte sedimentation rate (DAS28-ESR), the Simplified Disease Activity Index (SDAI), and the Clinical Disease Activity Index (CDAI). Subjective measurements, such as patient reported outcomes have been incorporated into several of these indices alongside more objective assessments, such as increases in the ESR and C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…These data show a difference in the proportion of patients with low disease activity, as assessed by CDAI and SDAI, compared with DAS28‐ESR. A previous study analyzing Dutch and Portuguese patient data from the Measurement of Efficacy of Treatment in the Era of Rheumatology (METEOR) database found a discordance between low disease activity defined by DAS28‐ESR and low disease activity defined by SDAI and CDAI . These differences may be due to the different weighting of the individual components between the assessment indices, including the heavier weighting of patient’s global assessment of disease activity in the CDAI and SDAI than in the DAS28‐ESR.…”
Section: Discussionmentioning
confidence: 99%
“…These data show a difference in the proportion of patients with low disease activity, as assessed by CDAI and SDAI, compared with DAS28‐ESR. A previous study analyzing Dutch and Portuguese patient data from the Measurement of Efficacy of Treatment in the Era of Rheumatology (METEOR) database found a discordance between low disease activity defined by DAS28‐ESR and low disease activity defined by SDAI and CDAI . These differences may be due to the different weighting of the individual components between the assessment indices, including the heavier weighting of patient’s global assessment of disease activity in the CDAI and SDAI than in the DAS28‐ESR.…”
Section: Discussionmentioning
confidence: 99%
“…By taking into account the swollen joint count (of 28 joints), tender joint count (of 28 joints), and the global assessments of disease activity (scored 0–10 on a visual analog scale) by both patient and clinician, the CDAI is scored on a scale ranging from 0 to 76 points [ 25 ]. The level of disease activity can be interpreted as low (2.9 ≤ CDAI ≤ 10), moderate (10 < CDAI ≤ 22), or high (22 < CDAI), while CDAI ≤ 2.8 indicates the state of remission [ 49 ]. A decrease in CDAI of at least 1 for patients with low disease activity; of at least 6 for patients with moderate disease activity; and of at least 12 for patients with high disease activity between two consecutive visits is considered as MCII in RA disease activity [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…However there is still discordance between them. It has been proposed that the DAS28-ESR and the CDAI/SDAI weights their individual components differently, which sometimes 22 We have used all the scoring systems and if found high score in any one of them we labelled the patient as having high disease activity. Anaemia was found in 69% of the population and 91.6% in the subset of patients of high disease activity, which was similar to observational study carried out by Goyal et al on 59 patients of RA in India which showed 67.8% of the patients had anaemia and 90% in the subset of patients of high disease activity.…”
Section: Discussionmentioning
confidence: 99%